Índice de pobreza multivariante a través de la III Encuesta Nacional de Presupuestos Famililares 2004-2005 (2016)
This study aimed to design a poverty index using a multivariate approach to create an alternative indicator that combines the beneﬁts of the existing indexes. The construction of this index is based on data supplied by the third National Household Budget Survey (NFPS) 2004-2005, where information on socioeconomic variables of Venezuelan households fall. Eight (8) dimensions with household characteristics and from there it deﬁned was created a single index which summarized the information from the diﬀerent dimensions for measuring poverty , allowing compare households that are classiﬁed in the same category.